The dynamic and heterogeneous effects of retirement on cognitive decline - Hendrik Schmitz; Matthias Westphal (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects. – – Wir untersuchen die Auswirkungen des Ruhestands auf die kognitiven Fähigkeiten (bis zu zehn Jahre nach der Verrentung) anhand von Daten aus 21 Ländern in Europa und den USA. Zu diesem Zweck kombinieren wir Ereignisstudienmethoden und den Modellrahmen der Marginal Treatment Effects um sowohl dynamische Effekte schätzen zu können, als auch je Bevölkerungsgruppe heterogene Effekte zu erkennen. Wir können dadurch zwei Effekte trennen: solche, die durch die reine Dauer des Ruhestands zunehmen, und solche, die sich dadurch ergeben, dass Personen mit unterschiedlichen Präferenzen unterschiedliche Renteneintrittszeitpunkte wählen. Unsere Ergebnisse deuten auf erhebliche negative Auswirkungen des Ruhestands auf die kognitiven Fähigkeiten hin. Wir beobachten auch eine Heterogenität der Effekte: Diejenigen, die so früh wie möglich in Rente gehen, erleben keine kognitiven Einbußen, während diejenigen, die später in Rente gehen, starke negative Effekte auf ihre kognitiven Fähigkeiten erleiden.
Keywords: C31; J14; J24; 330; Cognitive abilities; retirement; event study; marginal treatment effects